Geomorphic Patterns and Processes at Alpine Treeline - Butler, David R; Malanson, George P; Resler, Lynn M; Walsh, Stephen J; Wiklerson, Forrest D; Schmid, Ginger L; Sawyer, Carol F (Elsevier BV, 2009)
Geomorphic patterns and processes affect alpine treeline at a variety of spatial and temporal scales. At coarse scales, snow avalanches and debris flows are widespread and create disturbance treelines elevationally depressed well below the climate-controlled alpine treeline. At medium scales, turf-banked terraces create tread-and-riser topography that is a difficult landscape for a tree seedling to survive upon because of exposure to wind, dryness, and impenetrable surfaces. At fine scales, turf exfoliation of the fronts of turf-banked risers, and boulders, offer microsites where tree seedlings may find shelter and are able to gain a foothold in the alpine tundra; conversely, however, surfaces of needle-ice pans and frost heaving associated with miniature patterned ground production are associated with sites inimicable to seedling establishment or survival. The geomorphic role of animals at treeline may assist or hinder seedling survival.